The reality of employing the Internet of Things in the educational process from the point of view of faculty members in Saudi universities - Alharbi, Sarah Fahad; Altaf, Eiad AbdulAziz (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the reality of employing the Internet of Things in the educational process in Saudi universities by knowing the degree of readiness of Saudi universities to employ the Internet of things in the educational process and the importance of employing it, and the obstacles to employing it from the point of view of faculty members in Saudi universities. Through the application of a questionnaire (56) phrases that were applied to a sample of (382) faculty members in five Saudi universities representing the regions of the Kingdom of Saudi Arabia, the study showed several results, the most important of which was: The degree of readiness of Saudi universities to employ the Internet of Things in the educational process came The degree of employing the Internet of Things (IoT) in the educational process in Saudi universities from the point of view of faculty members was medium, with a high degree of (4.07) with a percentage of (62.61%) and a (high) degree of approval. The Internet of Things in the educational process (4.07), with a percentage of (81.4%), with a high degree of approval. The results also showed that there are obstacles that prevent the use of the Internet of Things; in the educational process in Saudi universities; Where the general average was equal to (4.03), with a percentage of (80.6%), and the degree of approval (high). The study recommended several recommendations, the most important of which are: Work to reduce the obstacles that prevent the use of the Internet of Things in the educational process.
Keywords: Internet of things; Saudi universities; educational technologies; e-learning